Conceptions of Europe in Renaissance France : essays in honour of Keith Cameron - Cameron, Keith; Cowling, David (David J.) (Faux titre ;, 2006)
This collection of essays by ten leading British and French Renaissance specialists explores, for the first time, differing conceptions of Europe in Renaissance France. Four essays concentrate on problems of definition in ideological, chronological, geographical and linguistic terms, concentrating on the relationship between Christendom and Europe, Antiquity and its Renaissance heirs, and Latin and the vernacular languages of south-western France. A further three essays address cultural exchange and political collaboration (and, inevitably, conflict) between France and England at the time of t.